The effects of tax incentives on job and income generation in the State of Maranhão (2021)
This study aims to verify the participation of the tax incentive granted to companies in the growth of per capita income in Maranhão. The programs analyzed were: “PróMaralhão and “ Mais Empresas” and the period verified was between 2010 and 2017. The methodology used was the analysis of data on the effects of tax incentives on the generation of employment and income from the Gross Domestic Product (GDP)) production, per capita available on the websites: Instituto Maranhense de Socioeconomic and Cartographic Studies (IMESC), Brazilian Institute of Geography and Statistics (IBGE) and Institute of Applied Economics Research (IPEA). The main results are a positive relationship between the growth of employment and income in the state of Maranhão, and that the policy adopted by the government in the granting of tax incentives, through the PróMarhões and Mais Empresas programs has contributed to economic growth, consequently, has generated some social and economic development for its citizens.